Validity And Reliability Of The Malay Versions Of The Posttraumatic Growth Inventory-Short Form, Hope Scale, Life Orientation Test-Revised And Source Of Social Support Scale In Cancer Patients - Md Sharif, Siti Shahanis (2020)
Background: There is a growing need to explore positive psychology in cancer patients as positive psychology may enhance well-being of patients. There are four important positive psychology’s components which may bring about positive outcomes in cancer patients i.e. posttraumatic growth (PTG), hope, optimism and spousal support. This study translated the Posttraumatic Growth Inventory- Short Form (PTGI-SF), Hope Scale (HS), Life Orientation Test-Revised (LOT-R) and Sources of Social Support Scale (SSSS) into Malay and investigated the psychometric properties of the Malay versions. Methods: Concurrent translation and back-translation of the English versions of the PTGI-SF, HS, LOT-R and SSSS were performed, and the Malay versions of the questionnaires were administered to 195 cancer patients of different cancer diagnoses at baseline and 2 months later at follow up assessment.